Posttraumatic Stress Disorder, Depression, and Prolonged Grief Disorder in Families Bereaved by a Traumatic Workplace Death: The Need for Satisfactory Information and Support - Matthews, Lynda R.; Quinlan, Michael G.; Bohle, Philip (Frontiers in Psychiatry, 2019)
The impact of traumatic workplace death on bereaved families, including their mental health and well-being, has rarely been systematically examined. This study aimed to document the prevalence and key correlates of probable posttraumatic stress disorder (PTSD), major depressive disorder (MDD), and prolonged grief disorder (PGD) in family members following a workplace injury fatality. The hidden nature of the target population necessitated outreach recruitment techniques, including the use of social media, newspaper articles, radio interviews, and contact with major family support organizations. Data were collected using a cross-sectional design and international online survey. The PCL-C (PTSD), the PHQ-8 (MDD), and PG-13 (PGD) were used to measure mental health disorders. All are well-established self-report measures with strong psychometric qualities. Participants were from Australia (62%), Canada (17%), the USA (16%) and the UK (5%). The majority were females (89.9%), reflecting the gender distribution of traumatic workplace deaths (approximately 90% of fatalities are male). Most were partners/spouses (38.5%) or parents (35%) and over half (64%) were next-of-kin to the deceased worker. The majority of deaths occurred in the industries that regularly account for more than 70 per cent of all industrial deaths – construction; manufacturing; transport; and agriculture forestry and fishing. At a mean of 6.40 years (SD = 5.78) post-death, 61 per cent of participants had probable PTSD, 44 per cent had probable MDD, and 43 per cent had probable PGD. Logistic regressions indicated that a longer time since the death reduced the risk of having each disorder. Being next-of-kin and having a self-reported mental health history increased the risk of having MDD. Of the related information and support variables, having satisfactory support from family, support from a person to help navigate the post-death formalities, and satisfactory information about the death, were associated with a decreased risk of probable PTSD, MDD, and PGD, respectively. The findings highlight the potential magnitude of the problem and the need for satisfactory information and support for bereaved families.